ANALISIS KOMUNIKASI PADA TAHFIDZ AL-QUR’AN DALAM PROSES MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN DARUL AMAN 05 LENGKESE KABUPATEN TAKALAR - St Hajar Said; Zelfia``` Zelfia; M.Nur Wakka (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2020)
The aims of this study are: (1) To find out the communication that occurs in the process of memorizing the Qur'an at the Darul Aman Islamic boarding school 05 Lengkese, Takalar district. (2) To find out the role of intrapersonal communication in the process of memorizing the Qur'an at the Darul Aman Islamic boarding school 05 Lengkese, Takalar district. . The type of research used in this thesis is a qualitative method. The results of this study indicate that intrapersonal communication carried out by students of tahfidz Al-Qur'an in a way that students can control themselves, motivate themselves, pray, be grateful, and reflect on themselves. The second interpersonal communication that occurs in the tahfidz of the Qur'an is by communicating with the ustadz/ustadzah about learning, dealing with problems, depositing memorization, communicating with fellow students, namely exchanging opinions, and others. Third, there is public communication, communication occurs at tahfidz Al-Qur'an, namely by means of ustadz/ustadzah or kiai giving lectures, providing direction, information, or motivating students, teaching Arabic, and others. The role of intrapersonal communication is very important, especially for tahfidz Al-Qur'an students, namely being able to get closer to God such as praying, being grateful and other intrapersonal communication can also motivate themselves, self-introspection or self-reflection.